POTENSI PENERAPAN KONSEP EKONOMI SIRKULAR UNTUK PENGEMBANGAN INDUSTRI TAHU YANG BERKELANJUTAN - Yulistika, Efri; Suprihatin, Suprihatin; Purwoko, Purwoko (Department of Agroindustrial Technology, Bogor Agricultural University, 2023)
Tofu is one of the products produced mainly by small and medium industries (SMEs). Along with the production of tofu by SMEs, there are many environmental problems. The industry's main ecological problems are waste management, efficient use of materials, water, and energy, and emissions generated during production. One solution that can be done to solve these problems is through the application of the circular economy concept. This research aimed to characterize the tofu production process, identify problems and analyze the potential application of the circular economy concept for the sustainable development of the tofu industry. The research was conducted through field observation and literature study. The research data were processed, analyzed, and presented in a qualitative descriptive manner. The results of the study show that the circular economy concept that can be adopted in the tofu industry A, B, and C is the utilization of solid waste in the form of tofu dregs as food ingredients (nuggets, tempe gembus, shredded and soy sauce), semi-finished foodstuffs (in the form of dregs flour which can be used as raw material for food processing such as crackers, pastries, and brownies), and as animal feed. Circular economy alternatives are analyzed by considering economic, environmental and social feasibility. Alternatives that are feasible and applicable to the tofu industry A, B, and C are washing soybeans in stages to reduce water use, tofu dregs are processed into tempe gembus or other products, cooking soybean porridge with boiler heating and cooking with a steam system, and liquid waste (whey) can be utilized as raw material for nata de soya, biogas and liquid fertilizer. Keywords: circular economy, tofu industry, sustainability